Perancangan Sistem Informasi Pengolahan Data Produksi TBS (Tandan Buah Segar) Kelapa Sawit Berbasis Material Requirement Planning Pada PT. Tanjung Jaya Lestari Lampung Tengah - Zohan Fanani; Wiwin Susanty (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2013)
Analysis of Data Processing System Analysis Method to determine the production data processing FFB (fresh fruit bunches) Oil Palm at PT. Tanjung Jaya Lestari presented in this thesis. This analysis is an attempt to facilitate the ability to run the system using a variety of systems and one of them is Data Processing System Production at PT. Tanjung Jaya Lestari. "How to create a system of data processing applications for the production of FFB (fresh fruit bunches) of oil palm in the PT. Tanjung Jaya Lestari so it can more quickly and accurately? ? " At this time, perform data processing in the production of the production is still done by recording in the general ledger. This resulted in the frequent occurrence of errors and duplication of data pose serious problems. The objective of this paper is to describe, illustrate, and report the results of research carried out and provide solutions to problems that are found to facilitate the processes performed during data processing FFB production sawit.penelitian flashing this gives an insight and direct experience in the world work, so that students can integrate theory and practice acquired in the lecture bench with the reality on the ground.